Advances in Nanofibre Research Volume 2 - Haghi, Akbar K. (ISmithers Rapra Pub., 2012)
Nanomaterials are the study of how materials behave when their dimensions are reduced to the nanoscale. It can also refer to the materials themselves that are used in nanotechnology. Materials reduced to the nanoscale can suddenly show very different properties compared to what they exhibit on a macroscale, enabling unique applications. The book offers scopes that have potential for applications in several disciplines of nano materials. Each chapter ranges from new methods to novel applications of existing methods to gain understanding of the material and/or structural behaviour of new and adv.
Keywords: Nanofibers.; Electrospinning.; Nanostructured materials.; Polymers -- Electric properties.; Textile fibers, Synthetic.; elektronické knihy; electronic books